1990
DOI: 10.1126/science.1693014
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of the Initiation-to-Elongation Transition by a Transdominant RNA Polymerase Mutation

Abstract: RNA polymerase, the principal enzyme of gene expression, possesses structural features conserved in evolution. A substitution of an evolutionarily invariant amino acid (Lys1065----Arg) in the beta subunit of Escherichia coli RNA polymerase apparently disrupts its catalytic center. The mutant protein inhibited cell growth when expressed from an inducible promoter. The assembled holoenzyme carrying the mutant subunit formed stable promoter complexes that continuously synthesized promoter-specific dinucleotides b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…This phenotype is reminiscent of rpoB mutations in Escherichia coli which render the holoenzyme unable to clear a promoter and are dominant lethal when expressed in vivo (20-22, 32, 46). It is thought that this phenotype results from mutant polymerases occupying and occluding genes, thereby preventing their efficient transcription by wild-type polymerase (20,32,46).…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype is reminiscent of rpoB mutations in Escherichia coli which render the holoenzyme unable to clear a promoter and are dominant lethal when expressed in vivo (20-22, 32, 46). It is thought that this phenotype results from mutant polymerases occupying and occluding genes, thereby preventing their efficient transcription by wild-type polymerase (20,32,46).…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic core of the bacterial enzyme, capable of normal elongation and termination, is made of two large ␤ and ␤Ј subunits and a dimer of ␣ subunits, which correspond to RPB2, RPB1, and a heterodimer of two RPB3/RPB5 subunits in the yeast Pol II, respectively (23,36). There is a vast pool of already known mutants of E. coli RNAP with altered elongation properties, and a well established genetic system makes it easy to obtain and characterize novel mutants (51). Moreover, the biochemical system allows for reconstitution of E. coli RNAP from either separately purified subunits or even separate domains within the subunits, which extends the list of manipulations possible with mutant RNAPs in vitro (52).…”
Section: Nucleosomes Form Similar Barriers To Assembled and Promoter-mentioning
confidence: 99%
“…although titred antibodies were used in the immunoprecipitation. The fact that the B3-4 segment is accessible is in keeping with the catalytic role of this region in the enzymatic reaction (Grachev et al 1987(Grachev et al , 1989Kashlev et al 1990;Lee et al 1991). Taken together, we would suggest the N-terminal half of ␤, in particular the region specified by segment B2, is generally 'buried' within the enzyme complex (previous studies have shown that a small number of particular epitopes are accessible; see, for instance, Severinov et al 1993).…”
Section: Figurementioning
confidence: 67%